Analysis of the Influence of Product Quality and Service Quality on Repurchase Intention with Customer Satisfaction as a Mediating Variable - Fifi Zulviani; Muthia Roza Linda (Jurnal Economic Resource, 2026)
This study examines the effects of product and service quality on repurchase intention, with customer satisfaction as a mediating variable, at Maetek Rattan Store in Padang City. Using a quantitative, descriptive, and causal design, data were collected from 112 respondents via questionnaires and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that product quality and service quality positively influence customer satisfaction and repurchase intention. Customer satisfaction mediates the relationship between service quality and repurchase intention, implying that better service and product quality can enhance customer loyalty and business competitiveness.